Any dream will do [compact disc, unabridged] : a novel - Macomber, Debbie (Macomber, Debbie. New beginnings series., 2017)
Troubled Shay and recently widowed Pastor Drew find the strength to overcome their painful histories. Now, they can face the challenge of learning to trust and love again--together. But it will take courage and faith for her and Drew to find healing and open their hearts to a brighter future.